Minimal asymptotic distributions for estimators of panel data models - Tiemen Woutersen (The University of Western Ontario, Department of Economics, 2002)
This paper develops the minimal asymptotic distributions for estimators of panel data models with incidental parameters
Keywords: C31; C14; C33; 330; incidental parameters; panel data